Perfusão do rim isolado de coelho: estudo comparativo da variação da concentração de albumina e efeitos renais da Enterotoxina Termoestável de Escherichia coli - Gomes, Victor Martins (2019)
Since the 1970s, physiologic research had been made on the prospect to discover a new signaling axis between the gastrointestinal system and renal system. Since then, research on the action of heat-stable Escherichia coli enterotoxin (STa), as described in 1983 by Fonteles and Lima, with the demonstration of caliuretic, natriuretic and diuretic effects, which already indicate a cross-talk between these two systems, led to the proposition of the existence of a hormone signaling in an entero-renal axis, for the excretion of the excess of ingested salt. Investigations with hormones of the guanylin class have been made in a model of rat perfused kidney, with a shortage of work in other phylogenetically more evolved animal models such as the rabbit. The objective of this study was to study rabbit kidney perfusion using a Krebs-Henseleit solution with different concentrations of albumin (0%, 2%, 4% and 6%), and the heat-stable Enteroxin, in order to evaluate the transport and the absorption of salt and water. Male New Zealand rabbits (800-1000 g) were anesthetized with urethane (1.2 g / kg, I.P) and pentobarbital (30 mg / kg, I.M). Surgery is then performed to isolate the left kidney of the animal, perfused it in situ initially, and then ex vivo, into a renal perfusion system as developed by Fonteles et al. In the 1980s. Urine and perfusate samples were collected within 10 minutes gap. After biochemical measurements for sodium and potassium contents, renal function parameters were calculated after administration of; heat-stable enterotoxin (7 ng/mL) in the perfusion system. Data were statistically compared using Student's t test and Analysis of Variance (ANOVA), with significance of p <5%. As an initial step in understanding of renal mechanisms with different concentrations of albumin in infusion, we obtained the greatest effects on electrolyte reabsorption proportional to the addition of albumin. The concentration of 6% in albumin was chosen to investigate the renal effects of STa on renal tubular transport. As result, the addition of STa at 40 minutes significantly modified the parameters: perfusion pressure balance, increased urinary flow and glomerular filtration rate, increased potassium reabsorption in the distal segments and decreased sodium reabsorption in the segments leading to higher sodium excretion and lower potassium excretion. Therefore, with regard to STa toxin, the greatest effects were obtained with the highest concentration of albumin, 6%, allowing the visualization of natriuretic and diuretic effects in the renal tubules in rabbit.